Bullying Trends Inside Sport: When Organized Sport Does Not Attract but Intimidates - Vveinhardt, Jolita; Fominiene, Vilija B. (Frontiers in Psychology, 2020)
Bullying is acknowledged by scientists as a huge and still unresolved problem in sport. By triggering stress-related emotions, they determine the behaviour of those experiencing bullying and cause various negative effects on their physical and mental health. However, in the presence of the tenacious trend in sports “to put one’s own house in order”, athletes, coaches, teams, and sports organizations themselves often do not emphasize bullying or state that they do not encounter the problem at all, and adheres to the belief that athletes may use negative emotions instrumentally in order to perform tasks given to them more effectively. The aim of this research was to reveal the determinants of the internal environment of sports organizations, causing trends of bullying in organized sport. To achieve the research aim, a qualitative research paradigm was chosen. The empirical study involved eight coaches working in organized sport in Lithuania. The survey was conducted using the semi-structured interview method. Data were analysed employing inductive content analysis. The presented research results encompass the transcriptions of interviews, which are conceptually divided into three main categories revealing coaches’ opinion on trends of bullying in organized sport, related to the sports organization’s internal environment. Categories identified during the study can be grouped at three levels. The micro level – interrelationships; the mezzo level – sports professionals’ (coaches’) behaviour; and the macro level – management of interrelationships. These results revealed which determinants of the sports organization’s internal environment can be favourable for emergence of bullying and its dynamics in both interrelationships among athletes and interrelationships between athletes and coaches. And these trends of bullying, revealed on the basis of the responses of coaches involved in the study, allow us to see harmful principles of coaching, bullying-promoting traditions of team/group leadership, existing in sport, and to predict how this may effect both the athlete himself, his environment and attractiveness of the sporting activity itself.